Gold/silver/gold trilayer films on nanostructured polycarbonate substrates for direct and label‐free nanoplasmonic biosensing. Issue 8 (24th May 2018) - López‐Muñoz, Gerardo A.; Estévez, M.‐Carmen; Vázquez‐García, Marc; Berenguel‐Alonso, Miguel; Alonso‐Chamarro, Julián; Homs‐Corbera, Antoni; Lechuga, Laura M.
Abstract : Ultrasmooth gold/silver/gold trilayer nanostructured plasmonic sensors were obtained using commercial Blu‐ray optical discs as nanoslits‐based flexible polymer substrates. A thin gold film was used as an adhesion and nucleation layer to improve the chemical stability and reduce the surface roughness of the overlying silver film, without increasing ohmic plasmon losses. The structures were physically and optically characterized and compared with nanostructures of single gold layer. Ultrasmooth and chemically stable trilayer nanostructures with a surface roughness <0.5 nm were obtained following a simple and reproducible fabrication process. They showed a figure of merit (FOM) value up to 69.2 RIU −1 which is significantly higher (more than 95%) than the gold monolayer counterpart. Their potential for biosensing was demonstrated by employing the trilayer sensor for the direct and refractometric (label‐free) detection of C‐reactive protein (CRP) biomarker in undiluted urine achieving a Limit of Detection (LOD) in the pM order. Abstract : Gold/silver/gold nanostructured sensors based on commercial Blu‐ray optical discs as substrates and with integrated microfluidics have been designed and optimized. Ultrasmooth and chemically stable trilayer nanoslit‐based nanostructures were obtained following a simple and reproducible fabrication process. The direct and label‐free detection of C‐reactive protein (CRP) biomarker in undiluted urine was achieved with a LOD in the pM order.